P04.06 TERT PROMOTER MUTATIONS CONTRIBUTE TO SUBSET PROGNOSTICATION OF LOWER GRADE GLIOMAS - Chan, A.K. (Oxford University Press, 2014)
Recurrent mutations in the promoter region of TERT (telomerase reverse transcriptase) have been found in various cancers including diffuse gliomas. Mutations lead to TERT upregulation and are associated with aggressive clinical behaviour in glioblastomas. However, the clinical significance of TERT promoter mutations in lower grade gliomas remains undetermined. The aim of this study is to evaluate the status of TERT promoter and the respective prognostic significance in a cohort of 181 lower grade gliomas comprising grades II and III astrocytomas, oligodendrogliomas and oligoastrocytomas. Mutually exclusive mutations in TERT promoter, C228T and C250T, were identified in 12/89 (14%) diffuse astrocytomas, 8/23 (35%) anaplastic astrocytomas, 13/18 (72%) oligodendrogliomas, 3/3 (100%) anaplastic oligodendrogliomas, 17/45 (38%) oligoastrocytomas and 2/3 (67%) anaplastic oligoastrocytomas. Mutations co-occurred with 1p/19q codeletion (p < 0.001), IDH mutation (p = 0.025) and are associated with oligodendroglial histology (p < 0.001). Kaplan-Meier's survival analysis showed that TERT promoter mutation (p = 0.017), IDH mutation (p = 0.004) and 1p/19q codeletion (p < 0.001) were associated with favorable overall survival. In the subset of 90 IDH mutated lower grade gliomas lacking 1p/19q codeletion, 16 TERT promoter mutated tumors exhibited longer overall survival (p = 0.017). Consistent with this observation, in the subset of 71 IDH mutated astrocytomas, 11 TERT promoter mutated tumors showed longer progression-free survival (p = 0.003) and overall survival (p = 0.005). In contrast, among the subset of 46 IDH wild type lower grade gliomas, TERT promoter mutation was associated with shorter progression-free survival (p = 0.001) and overall survival (p = 0.001). Similarly, in the subset of 37 IDH wild type lower grade gliomas with intact 1p/19q, 8 TERT promoter mutated tumors exhibited unfavorable progression-free survival (p = 0.005) and overall survival (p = 0.008). Our results indicate that when combined with IDH status, TERT promoter mutation contributes to prognostic subgroups of lower grade astrocytic tumors or 1p/19q intact lower grade gliomas and this may further refine future molecular classification of lower grade gliomas.